2015
DOI: 10.4155/bio.14.309
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolomics and Biomarkers of Aristolochic Acid Nephrotoxicity by UPLC-QTOF/HDMS

Abstract: The identified metabolites suggested that AA nephrotoxicity rats occurred perturbations in Krebs cycle, gut microflora metabolism, amino acid metabolism, purine metabolism and bile acid biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…5-HTP inhibited COX-2 expression through conversion to 5-methoxytryptophan (5-MTP) [52]. Based on metabolomic analysis, several studies have demostrated the metabolism disorders of various amino acid in animal models of AKI and CKD [54][55][56][57][58]. The significantly aberrant tryptophan level has extensively demonstrated in both animal models and patients with AKI or CKD [58][59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…5-HTP inhibited COX-2 expression through conversion to 5-methoxytryptophan (5-MTP) [52]. Based on metabolomic analysis, several studies have demostrated the metabolism disorders of various amino acid in animal models of AKI and CKD [54][55][56][57][58]. The significantly aberrant tryptophan level has extensively demonstrated in both animal models and patients with AKI or CKD [58][59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…As a holistic approach reflecting comprehensive changes of endogenous metabolites in bio-fluids and tissues, metabolomics has been widely applied to the study of the pathogenesis of nephrotoxicity or kidney diseases and discover new biomarkers as well as effect of drug intervention and therapeutic mechanism 14 . Metabolomic method was widely used to explore the nephrotoxicity induced by chemical drugs 5, 6 and natural products 710 . Traditional Chinese medicines (TCMs) have been used for the treatment of different kidney diseases for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…PAG is a metabolite influenced by gut flora. Prior studies using models of adenine and aristolochic acid renal damage, have reported an increased excretion of PAG in urine (Zhang et al 2015;Zhao et al 2015). In this study, the signal of PAG was one of the variables contributing to the separation of the FAIG-Mo group, but its intensity in urine decreased in comparison to the control group.…”
Section: Discussionmentioning
confidence: 49%